Diminishing high‐frequency directivity due to a source effect: Empirical evidence from small earthquakes in the Abruzzo region, Italy. Issue 10 (27th May 2016) - Pacor, F.; Gallovič, F.; Puglia, R.; Luzi, L.; D'Amico, M.
Abstract: The aim of this study is to investigate the directivity effects of 250 aftershocks (magnitudes 3–5.5) of the Mw 6.1 2009 L'Aquila earthquake (central Italy). To this end, we estimate the apparent source spectra at each station removing path and site effects inferred by standard Generalized Inversion Technique. Then, we evaluate the residuals between the apparent source spectra and the event mean source spectrum at selected frequencies. We investigate azimuthal and frequency dependence of the residuals for 40 events with the best station coverage. For most of events with the strongest directivity effect ( Mw 3.4–4.0), we observe a remarkable decrease of the directivity amplification at high frequencies, which has not yet been documented for such relatively small‐magnitude events. Since there is negligible distance dependence, we ascribe this observation to a source phenomenon such as significant small‐scale rupture propagation complexity. Key Points: First observation of frequency dependence of directivity effect in data from small earthquakes The directivity effect above the source corner frequency diminishes with increasing frequency Our observations suggest significant rupture‐propagation complexity even for small earthquakes